A multicentre 'end to end' dosimetry audit for cervix HDR brachytherapy treatment. Issue 2 (February 2015) - Palmer, Antony L.; Diez, Patricia; Gandon, Laura; Wynn-Jones, Andrea; Bownes, Peter; Lee, Chris; Aird, Edwin; Bidmead, Margaret; Lowe, Gerry; Bradley, David; Nisbet, Andrew
Abstract Purpose To undertake the first multicentre fully 'end to end' dosimetry audit for HDR cervix brachytherapy, comparing planned and delivered dose distributions around clinical treatment applicators, with review of local procedures. Materials and methods A film-dosimetry audit was performed at 46 centres, including imaging, applicator reconstruction, treatment planning and delivery. Film dose maps were calculated using triple-channel dosimetry and compared to RTDose data from treatment planning systems. Deviations between plan and measurement were quantified at prescription Point A and using gamma analysis. Local procedures were also discussed. Results The mean difference between planned and measured dose at Point A was −0.6% for plastic applicators and −3.0% for metal applicators, at standard uncertainty 3.0% (k = 1). Isodose distributions agreed within 1 mm over a dose range 2–16 Gy. Mean gamma passing rates exceeded 97% for plastic and metal applicators at 3% (local) 2 mm criteria. Two errors were found: one dose normalisation error and one applicator library misaligned with the imaged applicator. Suggestions for quality improvement were also made. Conclusions The concept of 'end to end' dosimetry audit for HDR brachytherapy has been successfully implemented in a multicentre environment, providing evidence that a high level of accuracy in brachytherapy dosimetry can be achieved.